Opinions on smoking and smoking cessation: A qualitative research [Sigara ve sigara bi{dotless}rakmaya i̇lişkin görüşler: Kalitatif bir araşti{dotless}rma] - AKVARDAR, YILDIZ (My University, 2014)
OBJECTIVE: The aim of this research is to determine the views on cigarettes, cessation of smoking for smokers and nonsmokers. MATERIAL AND METHODS: This research is the focus group investigation with 33 persons participating in Balçova's Heart Project (BAK). RESULTS: The smokers have described smoking mostly as a friend but nonsmokers have described smoking as illness, unsoundness and associated with death. The smokers have indicated that the causes of cigarette smoking are a way of coping in difficulty and being accepted as friends. All of them have said that the basic factor for cessation of smoking is self-control. Smokers have signified that service for cessation of smoking should be free, continuous and applied by experts. Informational meetings should have explanations of methods of cessation of smoking, affectivity in smoking cessation process and health differences after cessation smoking. CONCLUSION: Perceptions of cigarette smokers and nonsmokers are different. Services related to cessation of smoking should be free, continuous and given by experts. © 2014 by Turkish Thoracic Society.
Keywords: Qualitative research; Smoking; Smoking cessation